Topic Continuity in the Short Story “The Tortoise and the Hare”: A Pragmatic Approach - Silaban, Jelly Prima Krisnawati; Elchaira, Nadya; Deliana, Deliana (UIBU, 2025)
This study uses a discourse analysis approach to examine topic continuity in the well-known fable the Tortoise and the Hare. Based on Halliday and Hasan's cohesion theory and Givón's framework. The study investigates how linguistic devices like pronouns, repetition, and zero anaphora preserve narrative coherence. Using a qualitative descriptive method, the analysis shows that minimum interference and short referential distances are crucial for maintaining textual clarity. While definite and possessive pronouns aid in medium- and long-range topic tracking, zero anaphora and third-person pronouns are consistently employed to preserve local coherence. The results show that the fable's theme consistency is accomplished by the deliberate use of unified techniques that guarantee the traceability of characters and events rather than intricate frameworks. Notably, the text's emphasis on distinct protagonists is reflected in the lack of indefinite pronouns, which supports its didactic and moral goals. When paired with good reference management, the narrative's simplicity shows how cohesiveness can be efficiently achieved in brief textsThis study highlights how traditional tales model referential cohesiveness and use discourse strategies to support comprehension and learning. Additionally, the findings lay the groundwork for future comparative studies on topic continuity across languages and genres.